Sustainability indicators in milk production in an agrarian reform settlement in the north-central part of Paraná (Research, Society and Development, 2023)
The present study aimed to characterize and analyze aspects related to the sustainability of dairy farms belonging to a settlement of Agrarian Reform in the north-central region of Paraná. We analyzed 100 small properties, linked to "family-type agriculture", in the period from October 2019 to March 2020, through the application of semi-structured forms, with the purpose of collecting data regarding environmental, economic, social, techno-productive issues, milking health, pasture management and technical assistance. Descriptive statistical analysis and aggregate analysis techniques were used. The results show that of the 31 sustainability indicators analyzed, 14 were above the sustainability threshold (score 3 on a scale from 1 to 5), while 17 did not reach this threshold. These data point to a probable problem of survival of dairy cattle ranching in the medium and long term, if support strategies are not developed and solutions to the weaknesses identified in these productive systems are not developed.